2023
DOI: 10.3389/fitd.2023.1067595
|View full text |Cite
|
Sign up to set email alerts
|

In situ expression of Th17 immunologic mediators in American cutaneous leishmaniasis caused by Leishmania (V.) braziliensis and Leishmania (L.) amazonensis in the Brazilian Amazon

Abstract: American cutaneous leishmaniasis (ACL) presents a wide spectrum of clinical and immunopathological manifestations. In Brazil, Leishmania (L.) amazonensis[La] and Leishmania(V.)braziliensis[Lb] show the highest pathogenic potential for humans causing different clinical forms: localized cutaneous leishmaniasis (LCL : Lb/La), anergic diffuse cutaneous leishmaniasis (ADCL : La) and mucocutaneous leishmaniasis (MCL : Lb). ADCL and MCL are the most severe forms and infection leads to a cellular immune response at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Higher levels of IL-17 were found in ML lesions than CL, and in PBMCs from patients in relation to healthy individuals [46][47][48][49] . Furthermore, there is higher expression of IL-17A + cells in lesions of patients with DCL, compared to localized cutaneous leishmaniasis (LCL), as well as to healthy individuals and LCL from L.braziliensis-infected patients 23 . It was previously observed that in lesions of L. braziliensis-infected patients, CD4 +47,48 , CD8 +47 and CD14 +47 cells can be sources of IL-17.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher levels of IL-17 were found in ML lesions than CL, and in PBMCs from patients in relation to healthy individuals [46][47][48][49] . Furthermore, there is higher expression of IL-17A + cells in lesions of patients with DCL, compared to localized cutaneous leishmaniasis (LCL), as well as to healthy individuals and LCL from L.braziliensis-infected patients 23 . It was previously observed that in lesions of L. braziliensis-infected patients, CD4 +47,48 , CD8 +47 and CD14 +47 cells can be sources of IL-17.…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 derived from Th17 cells has been associated with the pathogenesis of L.major infection in BALB/c mice 21 , however, it has no impact on C57BL/6 mice 22 . IL-17 + cells have been associated with DCL caused by L. amazonensis 23 , but the underlying main source of this cytokine has not yet been revealed. Interestingly, in human leishmaniasis, the clinical presentations mediated by L. amazonensis, L. major and L. braziliensis infection associate with increased γδ T cells 24-30. ; and in experimental leishmaniasis, L. amazonensis infection in susceptible Sv129 mice induces the expansion of IL-17A producing γδ T cells, but not Th17 cells 31 .…”
Section: Introductionmentioning
confidence: 99%